What's Law Got To Do With It? The IWA and the Politics of State Power in British Columbia, 1935-1939 - Parnaby, Andrew (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1999)
In THE wake of President Roosevelt's New Deal for labour in the US, the International Woodworkers of America (IWA) experienced tremendous growth in Oregon and Washington. Fearing the arrival of the IWA in BC, the provincial government enacted the Industrial Conciliation and Arbitration (ICA) Act as a means to stanch the growth of militant industrial unionism. It was at the company town of BlubberBay, BC, that the ICA Act was tested for the first time as capital, labour, and the state struggled over the pith and substance of the new legislation. Drawing on the insights of critical legal theorists and neo-institutionalists, this article examines the multiple ways in which the state, law, and legal process shaped both the formation of the IWA and the nature of class struggle itself. In particular, it illustrates how the expansion of formal collective bargaining, as well as the age-old legal remedies available at common and criminal law, worked together to set limits and erect boundaries on collective working-class action and, in the end, forge a "responsible union."